SP0029 Phenotyping Neck Pain in Order to Personnalize the Treatment. (10th June 2014) - Revel, M.
Abstract : The first step of the diagnosis is to eliminate a specific disease: Infections, neoplastic conditions (bone and spinal cord) rheumatoid arthritis, spondylarthropathy, polymyalgia rheumatica, crystal depositions, ... All these diseases eliminated, the patient is presenting a common or regional neck pain. Considering all the situations of regional neck pain as a single disease is confusing. It is not the best way to optimize the treatments, mainly the rehabilitation. Adopting a simple classification could be clinically relevant. 1) Presence of a minor traumatism at the outset of the pain history: – Provide we are in whiplash grades 1 and 2 of the Quebec Task Force classification, mobilisation and strengthening exercises should be initiated soon. 2) Aged patient with obvious osteoarthritic changes in the cervical spine. – Pain is only induced when moving the neck, mainly in rotation. Provide there are no signs of myelopathy or radiculopathy, rehabilitation based on gentle mobilization and axial tractions can be usefull. – Pain is permanent, even during night. A pseudo inflammatory flare can be demonstrated by MRI images of oedema on end plates, or facet joints. NSAIDs and even corticosteroids have their best indication here. No indication of exercises. – C1/C2 location is a very disabling condition leading in some cases to a surgical fusion with excellent results. 3) The patient is younger with no changes on X rays. – Slight limitation of passive motion is observed generally in rotation with pain in the last degrees. We are probably at the first stage of unco vertebral and facet joints degeneration. Some beneficial effect of analgesics and NSAIDs This is the only situation where manipulations can be allowed. Exercises are indicated. – Passive motions are normal and painless. Pain is perceived after long postures in flexed position along the trapezius muscles. The patient is often a woman with a slim long neck. Analgesics have a mall effect Strengthening of the dorsal neck muscles should be indicated – Similar conditions with various locations of pain including headache and trigger points close to those observed in fibromyalgia. Sleep disturbance is often recorded. Better effect of antidepressants than analgesics, NSAIDs and rehabilitation. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.6314